Ruido ambiental y el nivel de aprendizaje en estudiantes del colegio Sagrado Corazón Iquitos 2023 - Chavez Suarez Danny Javier (2024)
The research analyzed the impact of environmental noise on the learning of students at Colegio Sagrado Corazón de Iquitos in 2023, with a sample of 153 female students from primary and secondary levels. Direct measurement and perception methodologies were employed for environmental noise, and teaching-learning and attitudinal criteria were used to assess the level of learning, in accordance with the Ministry of Education. Noise levels were recorded during school hours, comparing them with WHO and ECA standards. The results showed that noise levels exceeded recommended standards indoors with students by over 35 dB, and without students by over 30 dB, and outdoors by over 26 dB, potentially affecting learning. Despite high noise levels, teachers rated academic performance as outstanding. However, a correlation of 39.1% was found, classified as low, between noise and academic performance.